Konsep Religiusitas Masyarakat Adat Musi - Talaud - Satria Adhitama (Kamaya: Jurnal Ilmu Agama, 2023)
The many sects of belief grow and develop in Indonesia, making some people think that these beliefs are a deviant group. One of the beliefs that live in Indonesia is the Musi Indigenous belief in the Talaud Islands. This study aims to provide a clear and comprehensive picture of the concept of religiosity of the Adat Musi adherents in the Talaud Islands. This research is important because with a clear picture, it is hoped that negative views about the religion of the archipelago or the flow of belief in God Almighty will decrease. This research is a social research with constructivism paradigm and descriptive qualitative approach. The method of data collection was carried out by in-depth interviews. The concept of the religiosity of the Adat Musi can be seen from the teachings of the Adat Musi, the acceptance of revelation by Bawangin Panahal, the rituals of worship, and various kinds of rituals performed by its adherents, starting from the ritual of feeding babies (baptism), marriage rituals, and death rituals. In addition, the ritual of farming and the establishment of houses for the adherents is also an important ritual for the adherents of the Adat Musi. The most emphasized by Adat Musi is the farming ritual which consists of several stages, namely Mallintukku Harele, Mallintukku Wuallannna, and Umanna Amme Wakku.